2013
DOI: 10.1007/s10565-013-9256-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of metolachlor action due to alterations in cell cycle progression

Abstract: Metolachlor, a commonly used herbicide in the Midwestern USA, functions by inhibiting chlorophyll and protein synthesis in target plants. Herbicide exposure has led to detrimental effects in several organisms, affecting their growth and behavior; however, its mechanism of action in nontarget organisms is not yet clear. The EPA does not currently have enforceable regulations for maximal limits allowed in drinking water. Previous growth studies from our lab have demonstrated that increasing metolachlor concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…At present, studies have shown that environmental pollutions could induce cell cycle alteration. For example, organochlorine compounds significantly increased the number of MCF‐7 cells entering the S phase, herbicide butachlor‐treated human peripheral blood mononuclear PBMN cells exhibited an increase in sub‐G1 peak with concomitant reduction in G1 phase, and metolachlor decreased HepG2 cell number due to cell cycle arrest through alterations in Rb phosphorylation (Aube et al, ; Dwivedi et al, ; Lowry et al, ). However, the effect of endosulfan on endothelial cell cycle is not known.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies have shown that environmental pollutions could induce cell cycle alteration. For example, organochlorine compounds significantly increased the number of MCF‐7 cells entering the S phase, herbicide butachlor‐treated human peripheral blood mononuclear PBMN cells exhibited an increase in sub‐G1 peak with concomitant reduction in G1 phase, and metolachlor decreased HepG2 cell number due to cell cycle arrest through alterations in Rb phosphorylation (Aube et al, ; Dwivedi et al, ; Lowry et al, ). However, the effect of endosulfan on endothelial cell cycle is not known.…”
Section: Discussionmentioning
confidence: 99%
“…A study with human liver (HepG2) cells suggests that metolachlor inhibits cell proliferation, affecting progression through the S phase of the cell cycle and entrance into the G2 phase (Lowry, Greiner, Fretheim, Ubben, & Dhanwada, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Следовательно, можно предполагать, что увеличение количества этих фокусов обусловлено пролиферацией инициированных НДЕА гепатоцитов до детектируемых размеров. Данных о влиянии S -метолахлора на пролиферацию гепатоцитов в доступ- [10,11]. Снижение синтетических процессов в гепатоцитах связано с угнетением энергетического обмена метолахлором [12].…”
Section: результаты и обсуждениеunclassified